Soil and Plant Nitrogen Management Indices Related to Within-Field Spatial Variability - Remigiusz Łukowiak; Przemysław Barłóg; Jakub Ceglarek (Agronomy, 2024)
Field zones at risk of low nitrogen use efficiency (NUE) can be identified by analyzing in-field spatial variability. This hypothesis was validated by analyzing soil mineral nitrogen (Nmin) and several plant and soil N management indices. The research was conducted in Karmin (central Poland) during two growing seasons, with winter oilseed rape (2018/2019) and winter wheat (2019/2020). The study showed that the crop yield was positively related to Nmin. However, this N trait did not explain all the observed differences in the spatial variation of crop yield and plant N accumulation. In addition, the soil N management indices were more spatially variable during the growing season than the plant N management indices. Particularly high variability was found for the indices characterizing the N surplus in the soil-plant system. The calculated N surplus (Nb = N fertilizer input − N seed output) ranged from −62.8 to 80.0 kg N ha−1 (coefficient of variation, CV = 181.2%) in the rape field and from −123.5 to 8.2 kg N ha−1 (CV = 60.2%) in the wheat field. The spatial distribution maps also confirm the high variability of the parameters characterizing the post-harvest N surplus, as well as the total N input (soil + fertilizer) to the field with rape. The results obtained indicate that a field N balance carried out in different field zones allows a more accurate identification of potential N losses from the soil-plant system.